Analisis Faktor-Faktor Yang Mempengaruhi Wajib Pajak Orang Pribadi Yang Melakukan Pekerjaan Bebas Dalam Memenuhi Kewajiban Membayar Pajak (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Sukoharjo) - Yunistika, Santi; , Sri Murwanti, S.E., M.M (2015)
This study aims to analyze how much influence variable pay tax awareness, knowledge and understanding of tax laws, a good perception on the effectiveness of the tax system, and the service of fiscus on the willingness to pay taxes. The sampling method used in this study is convenience sampling to select a sample freely at will researcher. Respondents in this study is the individual taxpayer who performs registered in STO Sukoharjo. Methods of data analysis using multiple linear regression, whereas the hypothesis test using the F test, t test, and the coefficient of determination (R2). Based on the results of the analysis of this research shows that awareness of paying taxes, knowledge and understanding of tax laws, the tax authorities and services have a significant effect on the willingness to pay taxes. While a good perception on the effectiveness of the tax system does not significantly influence the willingness to pay taxes.